PENGOBATAN PENYAKIT KOLESTROL DENGAN MENGGUNAKAN EKSTRAK HERBAL DI INDONESIA - A REVIEW - Maharni Apriana; Rifqi Maulana Toni; Muhammad Choerul Huda; Zulva Mustofa Kamal; Rita Khoerunnisa; Allahuddin Allahuddin; Retna Ayu Septiani; Sayyid Rafli Ash-Shidiqi; Fera Anggraeni (Jurnal Buana Farma, 2022)
Health problems are one of the most complex problems, the sanitation process in improving health with various uses of plants in Indonesia. A country that will be rich in natural resources such as some herbal plant extracts. As a form of serious treatment to improve the health of cholesterol disease in Indonesia, namely herbal plant extracts by utilizing the active substances contained in these plants in the form of flavonoids, saponins, HMG Co-A reductase, phenolics, hypocholesterolemic curcumin, and Beta Sitosterol through both in vitro and in vivo tests, which have important properties in the cholesterol treatment process, such as improving public health in Indonesia.